Knowledge Regarding Health Hazards of Cytotoxic Agent Among Nurses Working at B.P. Koirala Memorial Cancer Hospital, Bharatpur, Chitwan (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Cytotoxic agent is a substance that kills cells, including cancer cells, which may stop cancer cells fromdividing and growing and may cause tumors to shrink in size. These may have carcinogenic, mutagenic or teratogeniceffects. Nurses are directly exposed to it while handling cytotoxic agents. Objective of the study was to find out the level ofknowledge regarding health hazards of cytotoxic agent among nurses working in B.P. Koirala Memorial Cancer Hospital,Bharatpur Chitwan.Method: A descriptive cross sectional study was conducted using non probability purposive sampling technique to collectthe information among 106 nurses. Self-administered structured questionnaire was used to collect data. Data were analyzedby using SPSS version 22 and descriptive and inferential statistics were used.Result: The finding of the study showed that the majority of respondents (48.10%) had